Efektivitas Pembelajaran Matematika Melalui Penerapan Model Learning Cycle Pada Siswa Kelas XI SMA Negeri 1 Sosopan - Abdul Rahim Syah; Adek Nilasari Harahap; Susi Sulastri Lubis (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to examine the effectiveness of the Learning Cycle model in mathematics learning for grade XI IPA 2 students at SMA Negeri 1 Sosopan during the first semester of the 2024–2025 academic year, involving 28 students (11 males and 17 females). The research employed a pre-experimental design with The One Group Pretest-Posttest Design and used the Multistage Sampling technique. The instruments included a learning achievement test, student activity observation sheets, and student response questionnaires. The results showed that the average pretest score of 23.75 (very low category) increased to 77.21 (high category) after implementing the Learning Cycle model, with a normalized gain of 0.70. A total of 89.29% of students achieved individual mastery, while student learning activities were categorized as good, and student responses toward learning were positive. Therefore, it can be concluded that the Learning Cycle model is effective in improving students’ mathematics learning outcomes in grade XI IPA 2 at SMA Negeri 1 Sosopan.